Bionic man – offender of criminal law - Lapienytė, Kristina; Latakaitė, Greta (Vilnius University Open Series, 2023)
The article aims to analyse who a bionic man is and whether a bionic person can be a subject of a criminal deed according to Criminal Code of the Republic of Lithuania.
Keywords: bionic man; bionics; criminal liability; Criminal Code of the Republic of Lithuania